Chromogenic detection of yam mosaic virus by closed-tube reverse transcription loop-mediated isothermal amplification (CT-RT-LAMP) - Nkere, C.K.; Oyekanmi, J.O.; Silva, G.; Bömer, M.; Atiri, G.I.; Onyeka, J.; Maroya, N.G.; Seal, S.E.; Kumar, P. Lava (Springer, 2018)
A closed-tube reverse transcription loop-mediated isothermal amplification (CT-RT-LAMP) assay was developed for the detection of yam mosaic virus (YMV, genus Potyvirus) infecting yam (Dioscorea spp.). The assay uses a set of six oligonucleotide primers targeting the YMV coat protein region, and the amplification products in YMV-positive samples are visualized by chromogenic detection with SYBR Green I dye. The CT-RT-LAMP assay detected YMV in leaf and tuber tissues of infected plants. The assay is 100 times more sensitive in detecting YMV than standard RT-PCR, while maintaining the same specificity.